New cranium of the endemic Caribbean platyrrhine, Antillothrix bernensis, from La Altagracia Province, Dominican Republic. Issue 106 (May 2017) - Halenar, Lauren B.; Cooke, Siobhán B.; Rosenberger, Alfred L.; Rímoli, Renato
Abstract: Recent paleontological collection in submerged caves in the eastern Dominican Republic has yielded new specimens of Antillothrix bernensis . Here we describe a complete cranium of an adult individual (MHD 20) and provide phenetic comparisons to other endemic Caribbean taxa and extant mainland platyrrhines using three-dimensional geometric morphometric methods (3DGM). Qualitative and quantitative comparisons support conclusions based on other recently described fossil material: Antillothrix has a dentition lacking clear dietary specialization, an elongated brain case with strong temporal lines, and a vertically oriented nuchal plane. MHD 20 shares a combination of traits with a previously published subadult specimen (MHD 01) including a deep depression at glabella, dorsoventrally elongated orbits, and a relatively large face. This shared morphology reinforces the taxonomic affinity of the two specimens, with differences between the two likely reflecting the younger ontogenetic age of MHD 01. Comparisons to the extant platyrrhines paint a complicated picture as the results of between-group principal components analyses (bgPCA) indicate that Antillothrix does not share a suite of morphological features exclusively with any one genus. Depending on which bgPC axes are visualized, and which subset of landmarks is included (i.e., only those describing the shape of the face/palate for inclusion of Xenothrix ), MHD 20 is most similar in shape to the atelids, Alouatta, Lagothrix, and Brachyteles, or an otherwise "empty" region of shape space. It groups neither with Cebus nor Callicebus, two taxa that Antillothrix has been associated with in previous studies based on much less complete material. The Antillothrix cranium does not exhibit any of the derived characters classically used to diagnose or define any single clade; rather its morphology shares features with multiple platyrrhine groups. This is consistent with the interpretation that Antillothrix preserves a primitive morphology, which accords with the hypothesis positing an early arrival of platyrrhines in the Caribbean.